"EFFECTS OF HIGH-SPEED DRILL NOISE ON DENTISTS' HEARING " - F.Akbakhanzadeh (Tehran University of Medical Sciences, 1978)
The study deals with noise problems associated with the use of air-turbine drills in dental practice. Noise level measurements were made on various types of dental handpieces, when operated free running and when used to cut tooth tissue. Hearing acuity tests were also undertaken in 12 randomly selected dental surgeons who have been using these drills for a number of years. The results indicate that although the danger to hearing from high speed drills is small, the possibility of hazardous effects-at least, for susceptible ears- is not excluded.